Unveiling Novel Lytic Bacteriophages as Natural Biocontrol Agents Against Multidrug-Resistant Escherichia coli: Isolation, Characterization, and In vitro Application - Tasdurmazli, Semra; Erdogdu, Berna; Saghrouchni, Hamza; Var, Isil; Melo, Luis D. R.; Ozbek, Tulin (SPRINGER, 2026)
The alarming findings presented in the latest WHO report on the global antimicrobial resistance crisis have redirected scientific attention toward phage-based approaches as a renewed line of defense against multidrug-resistant (MDR) bacteria. In this study, four bacteriophages infecting a MDR-Escherichia coli strain were isolated from water sources and subjected to detailed phenotypic and genomic characterization. All phages efficiently inhibited MDR-E. coli at MOIs of 0.1 and 0.01, showing high stability across a broad temperature (4-65 degrees C) and pH (4-10) range. TEM analysis revealed that all phages exhibited a podovirus-morphotype. At 4 degrees C, titers remained stable for 6 months, with only a 1-2 log reduction-over a year. Notably, phage Sem4 exhibited markedly stronger lytic activity than the phage cocktail, fully suppressing bacterial growth. In tap water, phage Sem4 treatment reduced bacterial counts from 10(7) to 7 x 10(4) CFU/mL within 8 h, with no detectable colonies at 24-48 h. Genomic analysis showed that these phages possess linear dsDNA genomes of 44,244-45,205 bp, with similar to 45% GC content. Phylogenetic and comparative analyses classified them as novel Vectrevirus members within the Molineuxvirinae subfamily of the Autographiviridae family, sharing less than 95% intergenomic similarity with known Vectrevirus species. No genes associated with antibiotic resistance, toxins, or lysogeny were detected. These findings underscore the potential of - phages as a promising candidate for the development of next-generation biocontrol strategies, especially marking the efficiency of Sem4 in water sanitation systems, paving the way for sustainable and targeted interventions against MDR bacterial contamination.
Keywords: Multidrug-resistant Escherichia coli; Bacteriophages; Biocontrol; Water sanitation; ANTIBIOTIC-RESISTANCE; PHAGE THERAPY; E.-COLI; STRAINS; COCKTAIL; O157H7; FOOD; Environmental Sciences & Ecology; Food Science & Technology; Microbiology; Virology